Multinational Andean Project. Report #13: Second Quarter Activity Report – 1999/00. Second Quarter Financial Report – 1999/00 - Hickson, Catherine J. (1999)
Multinational Andean Project. Canadian International Development Agency, Arrangement: 24846, RC/Project: 540/20080. Commitment: 189086, Supplier: G41000